Tourism Destination Competitiveness; SWOT Perspective, Aik Bual Central Lombok, Indonesia - Ahmad; Samsul Muslim; Mona Atika; Muhammad Nuh Ilyas; Taufiq Kurniawan (JMET: Journal of Management Entrepreneurship and Tourism, 2023)
This study aims to determine the distribution of tourism potential and comprehensively examine how the potential of bual tourism is explained based on its strengths and weaknesses. Case studies are research accommodated with a qualitative descriptive approach. Data is collected from reliable sources of information; People who know how aik bual tourism is formed and operates. The informants are village governments, youth representatives, and aik bual tourism activists. All collected data is then analyzed using the SWOT approach to be presented as the final result of the research report. The results showed that aik bual tourism is rich in natural and cultural resources. This power can be an advantage when maximally managed. Limited human resources who understand tourism literacy are important research findings. Therefore, solutive efforts are needed to anticipate these problems, for example through continuous training both by the government and initiated by the community.